2020
DOI: 10.12968/jowc.2020.29.sup12.s38
|View full text |Cite
|
Sign up to set email alerts
|

Effects of resveratrol on the growth and enzyme production of Stenotrophomonas maltophilia: a burn wound pathogen

Abstract: Objective: The purpose of this study was to identify the potential of resveratrol in inhibiting the growth and production of two enzymes, hyaluronidase and protease, in Stenotrophomonas maltophilia, which has become a burn wound pathogen of great significance. Method: Stenotrophomonas maltophilia (ATCC 17666) was cultured in nutrient broth and the microbial load was standardised to 0.5 McFarland standard at 600nm. The study included antimicrobial assays (well diffusion and resazurin dye binding method), hyalur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The blank tube contained all reagents except the tyrosine. The absorbance of the reaction tubes was measured colorimetrically at 660 nm (Bharadwaj and Vaidyanathan, 2020).…”
Section: Determination Of Specific Activity Of Protease Using Tyrosin...mentioning
confidence: 99%
“…The blank tube contained all reagents except the tyrosine. The absorbance of the reaction tubes was measured colorimetrically at 660 nm (Bharadwaj and Vaidyanathan, 2020).…”
Section: Determination Of Specific Activity Of Protease Using Tyrosin...mentioning
confidence: 99%
“…Infection is commonly observed in diabetic wounds, and its occurrence is related to many factors, such as local hyperglycemia and neuropathy, pathogen invasion, blood circulation disorder, severe inflammation, oxidative stress, local compression, trauma, etc. Stenotrophomonas maltophilia has become a frequently isolated bacterium in burn wounds and it has developed multidrug resistance (Bharadwaj & Vaidyanathan, 2020). Sraddha S et al (Bharadwaj & Vaidyanathan, 2020) resulted that resveratrol (1, 2, 3 and 5 mg/mL) could have an antimicrobial activity against stenotrophomonas maltophilia and they also indicated that resveratrol could reduce the levels of hyaluronidase, as well as protease, which were produced by stenotrophomonas maltophilia .…”
Section: Beneficial Effects and Underlying Mechanisms Of Resveratrol ...mentioning
confidence: 99%
“…Stenotrophomonas maltophilia has become a frequently isolated bacterium in burn wounds and it has developed multidrug resistance (Bharadwaj & Vaidyanathan, 2020). Sraddha S et al (Bharadwaj & Vaidyanathan, 2020) resulted that resveratrol (1, 2, 3 and 5 mg/mL) could have an antimicrobial activity against stenotrophomonas maltophilia and they also indicated that resveratrol could reduce the levels of hyaluronidase, as well as protease, which were produced by stenotrophomonas maltophilia . Alexei B et al (Shevelev et al, 2020) resulted that resveratrol could greatly suppress the reproductions of such bacteria or fungi as Staphylococcus aureus , Pseudomonas aeruginosa and Candida albicans , which are common pathogens that always adhered in wounds and blocked the healing process of wounds; furthermore, the developed tissue engineering biomaterials also promote the availability and efficiency of resveratrol to fight against infection.…”
Section: Beneficial Effects and Underlying Mechanisms Of Resveratrol ...mentioning
confidence: 99%
“…Compared to the latter two, RSV treatment resulted in a significant increase in the proportion of macrophages and fibroblasts, which became important in accelerating wound healing and restoring the normal stratification of the epidermis and hair follicles [ 67 ]. In addition, RSV had been found to be an effective compound against Stenotrophomonas in burn wounds [ 68 ]. It is thus clear that RSV could be a candidate for antimicrobial therapy.…”
Section: Mechanisms Underlying the Beneficial Effects Of Rsv On Wound...mentioning
confidence: 99%